2008
DOI: 10.4321/s0376-78922008000400001
|View full text |Cite
|
Sign up to set email alerts
|

Mamoplastia de aumento en doble plano: una alternativa subfascial en la optimización de las indicaciones

Abstract: Palabras clave Implantes mamarios subfasciales. Doble plano. Ondulaciones. Código numérico 5211-521140Proponemos el Doble Plano en la cirugía de aumento mamario como una alternativa a las indicaciones de uso del plano subfascial.Presentamos 30 casos en los que se utilizan variantes de la técnica en doble plano y discutimos sus indicaciones y ventajas a la vez que describimos detalles de la técnica.Este método consiste en crear un bolsillo donde el implante queda cubierto por el músculo pectoral solamente en su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…The subfascial pocket is a well-defined anatomical space that does not dissect the mammary parenchyma and allows good implant coverage while avoiding the dynamic breast. 50–52 In very thin patients, we used the subpectoral plane or the dual-plane modified by Ventura et al 29,51…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subfascial pocket is a well-defined anatomical space that does not dissect the mammary parenchyma and allows good implant coverage while avoiding the dynamic breast. 50–52 In very thin patients, we used the subpectoral plane or the dual-plane modified by Ventura et al 29,51…”
Section: Discussionmentioning
confidence: 99%
“…The subfascial pocket is a well-defined anatomical space that does not dissect the mammary parenchyma and allows good implant coverage while avoiding the dynamic breast. [50][51][52] In very thin patients, we used the subpectoral plane or the dual-plane modified by Ventura et al 29,51 A randomized controlled trial found a reduction in capsular contracture symptoms with the use of textured implants in the submuscular plane. 53 In our study, smooth and textured implants placed there had similar capsular contracture rates at the 1-year follow-up.…”
Section: Pocketmentioning
confidence: 99%
See 1 more Smart Citation
“…En otras técnicas de suspensión mamaria como la que presenta Ventura (11,12), el mecanismo se realiza utilizando al músculo pectoral mayor para crear un arrastre de las estructuras ligamentarias de la mama con el fin de recrear una ¨pexia por arrastre¨. A nuestro parecer, esta técnica es un soporte y sostén extra del tejido glandular, pero no provee protección a la cicatriz vertical ni sostén a la prótesis mamaria.…”
Section: Discussionunclassified
“…Son conocidos por todos los trabajos publicados por Tebbetts que dan origen a la técnica del Dual Plane, en la que se utilizan estas relaciones o vínculos anatómicos para generar correcciones dinámicas de la ptosis en mamoplastias de aumento (7). Conceptos que hemos valorado y adoptado, junto con otros colegas latinoamericanos (8)(9).…”
Section: Discussionunclassified